2014
DOI: 10.1371/journal.pone.0111848
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Oxya fuscovittata (Marschall) as an Alternative Nutrient Supplement in the Diets of Poecillia sphenops (Valenciennes)

Abstract: Growth of the ornamental fish industry is being hindered by the scarcity of low cost feed; hence alternative protein supplements should be explored. In this context the present study aims to evaluate whether the grasshopper Oxya fuscovittata could be used as a supplement for fish meal in the diets of Poecillia sphenops, which is one of the most common ornamental fishes worldwide. The present work is divided into three phases: In the first phase proximate composition of the grasshopper is obtained and five diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Many reports suggest that acridids can be used as protein supplement in formulation of fish and animal feed (Wang et al 2007;Anand et al 2008;Ganguly et al 2014). The major constraint of considering acridid meal as feed ingredient is its uncertain availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports suggest that acridids can be used as protein supplement in formulation of fish and animal feed (Wang et al 2007;Anand et al 2008;Ganguly et al 2014). The major constraint of considering acridid meal as feed ingredient is its uncertain availability.…”
Section: Discussionmentioning
confidence: 99%
“…Among the edible insects, short-horned grasshoppers have immense potential for biomass production as many of them are cultivable in mass scale under controlled condition (Haldar et al 1998;Anand et al 2008). Many reports have suggested for incorporation of grasshopper meal in fish and livestock feed (DeFoliart 1999;Anand et al 2008;Ganguly et al 2014). However, careful study is required to choose the appropriate species of grasshopper for the success of rearing because biomass producing capacity of an insect depends on several parameters such as host plants, environmental condition, sex ratio, biotic potential, survival rate, weight gain capacity etc.…”
Section: Introductionmentioning
confidence: 99%
“…Insect meals can be an optimal substitute of fish meal (Ganguly et al . ), without competing with use for human consumption. Moreover, artificial selection can also greatly improve the ability to adapt farmed fish to totally vegetal‐based feeds: which is almost a reality in Atlantic salmon farming (Le Boucher et al .…”
Section: The Role Of Scientific Research In Ornamental Animal Feedingmentioning
confidence: 99%
“…Fish meal replacement studies have started in ornamental fish nutrition, and soybean meal is the principal fish meal substitute (Velasco-Santamar ıa & Corredor-Santamar ıa 2011), with 30% of maximum inclusion level, depending on the species (Chong et al 2003). Insect meals can be an optimal substitute of fish meal (Ganguly et al 2014), without competing with use for human consumption. Moreover, artificial selection can also greatly improve the ability to adapt farmed fish to totally vegetal-based feeds: which is almost a reality in Atlantic salmon farming (Le Boucher et al 2012).…”
Section: Zooanthropological Considerations About Ornamental Fish Feedsmentioning
confidence: 99%
“…Studies revealed that grasshoppers are rich in protein, essential amino acids and other nutrients (Ganguly et al, 2013;Wang et al, 2007). Several reports suggested that dietary protein of fishmeal could be partially substituted in the fish diets with different grasshopper meal without compromising their growth, reproduction and feed utilisation efficiency (Balogun, 2011;Emehinaiye, 2012;Ganguly et al, 2014;Johri, Singh, & Johri, 2010). Oxya hyla hyla (Serville) is a multivoltine grasshopper distributed throughout the Indian subcontinent, and this species can be farmed for biomass production (Ghosh, Haldar, & Mandal, 2014, 2015.…”
Section: Introductionmentioning
confidence: 99%